Streaming Popularity: Analyzing the Competition of SVOD Brands in Achieving Preferences and Loyalty of Generation Z - Macnico, Peter; Christiarini, Renny; Purwianti, Lily (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This study investigates the impact of brand experience, brand trust, brand image and brand awareness on brand loyalty among Generation Z customers. As competition intensifies in the Subscription Video On Demand (SVOD) industry, particularly with Generation Z’s increasing influence, SVOD brands strive to differentiate themselves through distinct logos, enhanced user experiences, and intuitive applications. The research is set in the context of Batam, where 259 Generation Z customers participated in the study via a questionnaire distributed through Google Forms. The questionnaire employed a 5-point Likert scale to measure various brand-related factors. Respondents were selected using purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that brand experience has a significant positive impact on brand image, brand trust, and brand loyalty. Similarly, brand awareness positively affects both brand image and brand trust. However, brand awareness does not significantly influence brand loyalty, nor does brand trust significantly affect loyalty. Additionally, brand image has no significant impact on brand trust. The findings underscore the pivotal role of brand experience and brand image in fostering loyalty among Generation Z customers, offering valuable insights for SVOD brands aiming to enhance their market position.